Key factors of readiness in the implementation of Industrialised Building System (IBS) - Tamrin, Norhidayah; Mohd Nawi, Mohd Nasrun; Abdul Nifa, Faizatul Akmar (2016)
Although IBS has been introduced since the 1960, and many advantages that have identified for the implementation of IBS in Malaysia, yet the level of implementation of IBS still did not achieve the government target.Previous studies have been conducted to identify the factors that contribute to the lack of the implementation.From the previous studies, mostly the barriers of IBS implementation are rooted within the several semi-structured lack of readiness among industry players.The interview participants for this study are from the multidisciplinary IBS practitioners. This paper discusses the identified readiness with the objective to determine what the key factor of readiness in IBS implementation is and how far the factors influence the IBS activities.From the finding, the readiness factor was divided into three main factors which are knowledge, ability and planning.